An Examination of How Counselor Professionals Perceive the Role of Ict in Making Counseling Services More Accessible and Inclusive - Hassan, Ahmed Taiye; Bolaji, Hameed Olamilekan; Abdulkareem , Habibat Bolanle (Indonesian Journal of Educational Science and Technology, 2024)
This study scrutinizes counselors perceptions regarding the role of Information and Communication Technology (ICT) in advancing accessibility and inclusivity within Counselling services. A total of 159 counselor professionals participated in the survey, with 124 males and 35 females. The analysis of mean scores displayed a noteworthy variance between male (M = 3.845, SD = 1.39841) and female (M = 3.50013, SD = 1.50923) counsellor professionals' perceptions regarding ICT's influence on enhancing accessibility and inclusivity. The statistical examination utilizing an ANOVA test indicated a non-significant difference between the perceptions of male and female professionals (F-cal. = 1.726, df_between = 3, df_within = 2, p = .415). Consequently, the null hypothesis revealed no significant variance in perceptions based on gender was accepted.